Direct MicroCT imaging of non-mineralized connective tissues at high resolution. (8th January 2014) - Naveh, Gili R. S.; Brumfeld, Vlad; Dean, Mason; Shahar, Ron; Weiner, Steve
Abstract: The 3D imaging of soft tissues in their native state is challenging, especially when high resolution is required. An X-ray-based microCT is, to date, the best choice for high resolution 3D imaging of soft tissues. However, since X-ray attenuation of soft tissues is very low, contrasting enhancement using different staining materials is needed. The staining procedure, which also usually involves tissue fixation, causes unwanted and to some extent unknown tissue alterations. Here, we demonstrate that a method that enables 3D imaging of soft tissues without fixing and staining using an X-ray-based bench-top microCT can be applied to a variety of different tissues. With the sample mounted in a custom-made loading device inside a humidity chamber, we obtained soft tissue contrast and generated 3D images of fresh, soft tissues with a resolution of 1 micron voxel size. We identified three critical conditions which make it possible to image soft tissues: humidified environment, mechanical stabilization of the sample and phase enhancement. We demonstrate the capability of the technique using different specimens: an intervertebral disc, the non-mineralized growth plate, stingray tessellated radials (calcified cartilage) and the collagenous network of the periodontal ligament. Since the scanned specimen is fresh an interesting advantage of this technique is the ability to scan a specimen under load and track the changes of the different structures. This method offers a unique opportunity for obtaining valuable insights into 3D structure–function relationships of soft tissues.